Detection of novel syntrophic acetate‐oxidizing bacteria from biogas processes by continuous acetate enrichment approaches. Issue 4 (4th December 2017) - Westerholm, Maria; Müller, Bettina; Singh, Abhijeet; Karlsson Lindsjö, Oskar; Schnürer, Anna
Summary: To enrich syntrophic acetate‐oxidizing bacteria (SAOB), duplicate chemostats were inoculated with sludge from syntrophic acetate oxidation (SAO)‐dominated systems and continuously supplied with acetate (0.4 or 7.5 g l −1 ) at high‐ammonia levels. The chemostats were operated under mesophilic (37°C) or thermophilic (52°C) temperature for about six hydraulic retention times (HRT 28 days) and were sampled over time. Irrespective of temperature, a methane content of 64–69% and effluent acetate level of 0.4–1.0 g l −1 were recorded in chemostats fed high acetate. Low methane production in the low‐acetate chemostats indicated that the substrate supply was below the threshold for methanization of acetate via SAO. Novel representatives within the family Clostridiales and genus Syntrophaceticus (class Clostridia) were identified to represent putative SAOB candidates in mesophilic and thermophilic conditions respectively. Known SAOB persisted at low relative abundance in all chemostats. The hydrogenotrophic methanogens Methanoculleus bourgensis (mesophilic) and Methanothermobacter thermautotrophicus (thermophilic) dominated archaeal communities in the high‐acetate chemostats. In line with the restricted methane production in the low‐acetate chemostats, methanogens persisted at considerably lower abundance in these chemostats. These findings strongly indicate involvement in SAO and tolerance to high ammonia levels of the species identified here, and have implications for understanding community function in stressed anaerobic processes. Abstract : To enrich syntrophic acetate‐oxidising bacteria (SAOB), duplicate chemostats were inoculated with sludge from syntrophic acetate oxidation dominated systems and continuously supplied with acetate at high‐ammonia levels. Novel representatives within the family Clostridiales and genus Syntrophaceticus (class Clostridia) were identified to represent putative SAOB candidates in mesophilic and thermophilic conditions, respectively.